2013
DOI: 10.1302/0301-620x.95b7.30904
|View full text |Cite
|
Sign up to set email alerts
|

Total knee replacement with retention of both cruciate ligaments

Abstract: We report on the long-term results of 163 bicruciate-retaining Hermes 2C total knee replacements in 130 patients at a mean follow-up of 22.4 years (20.3 to 23.5). Even when the anterior cruciate ligament had a partially degenerative appearance it was preserved as long as the knee had a normal anterior drawer and Lachman's test pre-operatively. The description and surgical technique of this minimally constrained prosthesis were published in 1983 and the ten-year clinical results in 1999. A total of 12% of the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 43 publications
5
55
1
1
Order By: Relevance
“…However, the overall risk of revision was also higher in the BCR group (5% versus 1%). In the longest reported followup study on BCR knees, Sabouret et al [23] reported a survival rate of 82% with revision surgery as the endpoint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the overall risk of revision was also higher in the BCR group (5% versus 1%). In the longest reported followup study on BCR knees, Sabouret et al [23] reported a survival rate of 82% with revision surgery as the endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…The implant failures included 10 with loose tibial implants. Neither Sabouret et al [24] nor Townley [23,26] commented on the early complication or reoperation nor the potential for a learning curve effect early in the operative experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the BCR was compared to the CR in 91 patients, seven patients did not express a preference, 17 (18.7%) felt the CR implant was better and 67 (73.6%) felt that the BCR was better (5). When evaluating long-term results of a BCR design, survival rate using revision for any reason as the endpoint was 82% at 22.4 years (6).…”
mentioning
confidence: 99%